De Kerk en het Rechthuis van Westzaan. Johan Samuel Creutz buiten de poorten. De bijdrage van het Amsterdamse bouwvak tot de architectonische modernisering van een Noordhollands dorp (Bulletin KNOB, 1997)
In the eighteenth century, at a forty years' interval, two large new buildings arose at Westzaan, a small village in the Zaan region northwest of Amsterdam, dominating the village silhouette to this day. One is a good example of the so-called 'New Flamboyance' of the middle of the century, the other of the 'Noble Simplicity' succeeding it as a reaction some decades later.In 1740-'41 the medieval church was first replaced by a new building in Rococo style: only the existing tower was preserved, which was however to collapse in 1843. The new church acquired a ground plan in the form of a Greek cross, a form going back to the Noorderkerk in Amsterdam (1620-'23) by Hendrick de Keyser.Elements characteristic of the rococo-period are the rounded-off corners of the arms of the cross, and the elegant Dutch gable above the right-angled closure of the east wall; the latter had originally been intended to be repeated at the transept gables. Subsequently, between 1781 and 1783 a new court-house appeared, commissioned by the bailiff and secretary of the judicial district, Simon Jongewaard jr., next to the church in the place where a simpler building had preceded it.The design of the court-house had been made by the Amsterdam town architect Johan Samuel Creutz. It was a very small, but also very modern building in neo-Classicist style which owes its significance to the peristyle of (four) detached columns at the front, the first of its type realized in The Netherlands.However, at the same time the court-house still possessed many elements which were characteristic of Baroque and Rococo, such as the linking in pairs of the portico columns, the rounded-off corners and the elegant cupola on the roof with its buttresses swerving out concavely. The cube-shaped building has two floors, of which the general layout and decoration have been well preserved in general.It has been suggested that the Court-house of Westzaan is a simplified version of a project Creutz may have submitted for the prize contest for the new Town Hall of Groningen in 1774, because there a portico had been explicitly required. However, apart from this portico the design with the motto of Honor Vitae Delicia, which for graphological and orthographical reasons can probably be attributed to Creutz, shows few similarities.What’s striking about this latter plan is notably the cupola crowned with an obelisk - a kind of Pickelhaube - possibly to be traced back to the book of examples of De Neufforge. The cupola and the general layout of the facade of the Court-house itself are more likely to have been inspired by a contemporary print of an (unknown) Italian church facade which was to be included in a Dutch print work in 1786.